Metals & alloys in the unified numbering system. (SAE International : ASTM International, 2017)
"The Unified Numbering System for Metals and Alloys (UNS) provides a means of correlating many internationally used metal and alloy numbering systems currently administered by technical societies, trade associations, and those individual users and producers of metals and alloys."--Page vii
"SAE HS-1086/2017."
"ASTM DS-56L."
Keywords: Metals -- Notation.; Alloys -- Notation.; elektronické knihy; electronic books